2015
DOI: 10.1158/1078-0432.ccr-14-1661
|View full text |Cite
|
Sign up to set email alerts
|

Rilotumumab Exposure–Response Relationship in Patients with Advanced or Metastatic Gastric Cancer

Abstract: Purpose: Rilotumumab is an investigational, fully human monoclonal antibody to hepatocyte growth factor. In a randomized phase II study, trends toward improved survival were observed with rilotumumab (7.5 or 15 mg/kg) plus epirubicin, cisplatin, and capecitabine (ECX) versus placebo plus ECX in gastric/gastroesophageal junction (GEJ) cancer patients, especially in MET-positive patients. Here, we quantitatively characterized the longitudinal exposure-response [tumor growth (TG) and overall survival (OS)] relati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 34 publications
0
17
0
1
Order By: Relevance
“…To date, several notable E-R analyses in different cancer types have considered a range of clinical endpoints, including overall survival (OS), progressionfree survival (PFS; refs. [2][3][4][5][6], and overall response rate (ORR)/ tumor kinetics (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). The registration of pembrolizumab for the treatment of melanoma and non-small cell lung cancer (NSCLC) at the dose of 2 mg/kg administered once every 3 weeks (Q3W) was supported by dose-response analyses and model-based E-R analyses of longitudinal tumor size (10,17) using techniques adapted from earlier work (7,18).…”
Section: Introductionmentioning
confidence: 99%
“…To date, several notable E-R analyses in different cancer types have considered a range of clinical endpoints, including overall survival (OS), progressionfree survival (PFS; refs. [2][3][4][5][6], and overall response rate (ORR)/ tumor kinetics (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). The registration of pembrolizumab for the treatment of melanoma and non-small cell lung cancer (NSCLC) at the dose of 2 mg/kg administered once every 3 weeks (Q3W) was supported by dose-response analyses and model-based E-R analyses of longitudinal tumor size (10,17) using techniques adapted from earlier work (7,18).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have demonstrated that MET kinase inhibitor PHA-665752 causes arrest in cell proliferation and apoptosis in gastric cancer cells with constitutively activated MET whereas gastric cancer cells without constitutively activated MET were unaffected (109). Currently, AMG102 (rilotumumab) and MetMAb and PRO143966 (onartuzumab) are under active investigation as MET-targeting agents (56,(110)(111)(112). New results from a phase III study of AMG102 indicate that patients with advanced GEC treated with AMG102 adjunct to standard chemotherapy did not have improved OS compared to patients treated with chemotherapy alone.…”
Section: Gastroesophageal Cancer (Gec)mentioning
confidence: 99%
“…Rilomet-1 (NCT01697072) study attempted to evaluate the addition of rilotumumab to standard cisplatin and capecitabine chemotherapy as a first-line therapy for patients with advanced MET-positive GC or GEJ adenocarcinoma [73,74]. Rilotumumab is a human monoclonal antibody against c-MET (HGFR) factor.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%